Suppression of murine tumour growth through CD8+ cytotoxic T lymphocytes via activated DEC‐205+ dendritic cells by sequential administration of α‐galactosylceramide in vivo. Issue 3 (18th April 2017) - Kogo, Hideki; Shimizu, Masumi; Negishi, Yasuyuki; Uchida, Eiji; Takahashi, Hidemi
Summary: Cancer immunity is mediated through the effective priming and activation of tumour‐specific class I MHC molecule‐restricted CD8 + cytotoxic T lymphocytes (CTLs). DEC‐205 + dendritic cells (DCs) can cross‐present the epitope(s) of captured tumour antigens associated with class I MHC molecules alongside co‐stimulatory molecules to prime and activate tumour‐specific CD8 + CTLs. Immunosuppressive tolerogenic DCs with reduced co‐stimulatory molecules may be a cause of impaired CTL induction. Hepa1‐6‐1 cells were established from the mouse hepatoma cell line Hepa1‐6; these cells grow continuously after subcutaneous implantation into syngeneic C57BL/6 (B6) mice and do not prime CD8 + CTLs. In this study, we show that the growth of ongoing tumours was suppressed by activated CD8 + CTLs with tumour‐specific cytotoxicity through the administration of the glycolipid α ‐galactosylceramide ( α ‐GalCer), which is a compound known to stimulate invariant natural killer T (iNKT) cells and selectively activate DEC‐205 + DCs. Moreover, we demonstrated that sequential repetitive intraperitoneal inoculation with α ‐GalCer every 48 hr appeared to convert tolerogenic DEC‐205 + DCs into immunogenic DCs with a higher expression of co‐stimulatory molecules and a stronger cross‐presentation capacity, which primed CTL precursors and induced tumour‐specific CD8 + CTLs within the tumour environment without activating iNKT cells. These findings provide a new basis for cancer immunotherapy to convert tolerogenic DEC‐205 + DCs within tumours into immunogenic DCs through the sequential administration of an immuno‐potent lipid/glycolipid, and then activated immunogenic DCs with sufficient expression of co‐stimulatory molecules prime and activate tumour‐specific CD8 + CTLs within the tumour to control tumour growth. Abstract : The growth of ongoing tumours was suppressed by activated CD8 + cytotoxic T lymphocytes (CTLs) with tumour‐specific cytotoxicity through the administration of the glycolipid α ‐galactosylceramide ( α ‐GalCer). Sequential repetitive intraperitoneal inoculation with α ‐GalCer every 48 hr appeared to convert tolerogenic DEC‐205 + dendritic cells (DCs) into immunogenic DCs with a higher expression of co‐stimulatory molecules and a stronger cross‐presentation capacity, which primed CTL precursors and induced tumour‐specific CD8 + CTLs within the tumour environment. These findings provide a new basis for cancer immunotherapy to convert tolerogenic DEC‐205 + DCs within tumours into immunogenic DCs through the sequential administration of an immuno‐potent lipid/glycolipid, and then activated immunogenic DCs with sufficient expression of co‐stimulatory molecules prime and activate tumour‐specific CD8 + CTLs within the tumour to control tumour growth.